![](https://www1.michaeldemichele.com/img/nextpage1.png)
Suggested: sin3a+cos3a/sina+cosa=1-sina cosa - sin3a=cos3a - cos^3a.cos3a+sin^3a.sin3a=cos^3a 2a - sina+sin3a+sin5a+sin7a/cosa+cos3a+cos5a+cos7a=тан4а - sina+sin3a+sin5a/cosa+cos3a+cos5a=tan3a - cos7a+cos3a-cos5a-cosa/sin7a-sin3a-sin5a+sina - prove that sin4a=4sin cos3a-cosa sin3a - 4 sin^3a*cos3a+4cos3a*sin3a - sina-sin3a+sin5a-sin7a/cosa-cos3a-cos5a+cos7a=cos 2 a - prove that sin 4a=4sina cos3a-cosa sin3a - 4sin a.cos3a-4 cosa.sin3a - sin3a/sina-cos3a/cosa=2 - cos3a+sin3a/cosa-sina=1+2sin2a - sina+sin3a/cosa+cos3a=tan2a - sin3a+cos3a Browse related:
privacy contact
Copyright 2017 bapse
bapse is powered by Google and Youtube technologies
Thank you, for using bapse.
This site was designed and coded by Michael DeMichele,
and is being used as a portfolio demonstration. View more.